A novel non-invasive monitoring assay of 5-azacitidine efficacy using global DNA methylation of peripheral blood in myelodysplastic syndrome - Asano M; Ohyashiki JH; Kobayashi-Kawana C; Umezu T; Imanishi S; Azuma K; Akahane D; Fujimoto H; Ito Y; Ohyashiki K (Dove Medical Press, 2019)
Michiyo Asano,1 Junko H Ohyashiki,2 Chiaki Kobayashi-Kawana,1 Tomohiro Umezu,1,3 Satoshi Imanishi,3 Kenko Azuma,3 Daigo Akahane,1 Hiroaki Fujimoto,1 Yoshikazu Ito,1 Kazuma Ohyashiki11Department of Hematology, Tokyo Medical University, Tokyo, Japan; 2Department of Advanced Cellular Therapy, Tokyo Medical University, Tokyo, Japan; 3Department of Molecular Oncology, Institute of Medical Science, Tokyo Medical University, Tokyo, JapanPurpose: Monitoring response and resistance to 5-azacitidine (AZA) is essential when treating patients with myelodysplastic syndrome (MDS). To quantify methylated DNA not only in the promoter region but also in the gene body, we established a single-molecule methylation assay (SMMA).Patients and methods: We first investigated the methylation extent (expressed as methylation index [MI]) by SMMA among 28 MDS and 6 post-MDS acute myeloid leukemia patients. We then analyzed the MI in 13 AZA-treated patients.Results: Whole-blood DNA from all 34 patients had low MI values compared with healthy volunteers (P<0.0001). DNA hypomethylation in MDS patients was more evident in neutrophils (P=0.0008) than in peripheral mononuclear cells (P=0.0713). No consistent pattern of genome-wide DNA hypomethylation was found among MDS subtypes or revised International Prognostic Scoring System (IPSS-R) categories; however, we found that the MI was significantly increased for patients at very high risk who were separated by the new cytogenetic scoring system for IPSS-R (P=0.0398). There was no significant difference in MI before AZA, regardless of the response to AZA (P=0.8689); however, sequential measurement of MI in peripheral blood demonstrated that AZA non-responders did not have normalized MI at the time of next course of AZA (P=0.0352).Conclusion: Our results suggest that sequential SMMA of peripheral blood after AZA may represent a non-invasive monitoring marker for AZA efficacy in MDS patients.Keywords: myelodysplastic syndrome, azacytidine, peripheral blood, methylation index